Sketching A New Approach to American Studies - Lap, Ngo Tu (VNU Journal of Science: Education Research; Vol 34 No 2DO - 10.25073/2588-1159/vnuer.4139, 2018)
This paper analyzes briefly the theoretical frameworks developed by major thinkers in American Studies (Alexis de Toccqueville, Israel Zangwill, Max Weber, Frederick Jackson Turner) and proposes a new theoretical framework that approaches the USA as the biggest, earliest, and the most successful Special Free Economic Zone in the world history.